(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Present study was conducted to evaluate the effect of arsenic and its interaction with phosphorus (P) on root and shoot growth, chlorophyll contents and leaf protein at seedling stage under hydroponic culture. Three cultivars of rice BR-26, BR-3 and BRRI- 45 were used in this study. Arsenate significantly reduced root and shoot growth and chlorophyll content in all the cultivars. However leaf protein increased in BR-26, BR-3 and reduced in BRRI-45. Combined treatment of As and P significantly increased root and shoot length. Significant reduction of As toxicity was observed in hydroponic rice cultivars treated with As and P together. It may be said that P plays a vital role in the reduction of As contamination of rice and the results show that BR-26 is relatively tolerant to arsenate with respect to the root-shoot growth and leaf protein. J. Asiat. Soc. Bangladesh, Sci. 40(1): 141-150, June 2014